Autoimmune Ataxia During Maintenance Therapy for Acute Lymphoblastic Leukemia. (14th December 2018) - Voeller, Julie; Ikonomidou, Chrysanthy; Brucker, Justin; Diamond, Carol; Frierdich, Sharon; Patel, Neha
Neurologic dysfunction during acute lymphoblastic leukemia treatment is commonly associated with chemotherapy. Nonchemotherapy contributions should be considered for persistent atypical symptoms. We describe a boy with acute lymphoblastic leukemia who developed recurrent fevers, diarrhea, progressive ataxia, and neuropsychiatric impairment during maintenance chemotherapy. He was found to have cytomegalovirus in his serum and colon, but not in his cerebrospinal fluid. Instead, his cerebrospinal fluid revealed oligoclonal bands not present in the serum, suggesting an autoimmune process. Prompt treatment with ganciclovir and immunotherapy resulted in marked clinical improvement. Early recognition and treatment of an autoimmune encephalitis is paramount for optimal clinical outcome.